Dietary Zinc and Risk of Prostate Cancer in Spain: MCC-Spain Study - Enrique Gutiérrez-González (Nutrients, 2018)
Zinc is a key trace element in normal prostate cell metabolism, and is decreased in neoplastic cells. However, the association between dietary zinc and prostate cancer (PC) in epidemiologic studies is a conflicting one. Our aim was to explore this association in an MCC-Spain case-control study, considering tumor aggressiveness and extension, as well as genetic susceptibility to PC. 733 incident cases and 1228 population-based controls were included for this study. Dietary zinc was assessed using a food frequency questionnaire, and genetic susceptibility was assessed with a single nucleotide polymorphisms (SNP)-based polygenic risk score (PRS). The association between zinc intake and PC was evaluated with mixed logistic and multinomial regression models. They showed an increased risk of PC in those with higher intake of zinc (Odds Ratio (OR) tertile 3vs1: 1.39; 95% Confidence interval (CI):1.00⁻1.95). This association was mainly observed in low grade PC (Gleason = 6 RRR tertile 3vs1: 1.76; 95% CI:1.18⁻2.63) as well as in localized tumors (cT1-cT2a RRR tertile 3vs1: 1.40; 95% CI:1.00⁻1.95) and among those with higher PRS (OR tertile 3vs1: 1.50; 95% CI:0.89⁻2.53). In conclusion, a higher dietary zinc intake could increase the risk of low grade and localized tumors. Men with higher genetic susceptibility might also have a higher risk of PC associated with this nutrient intake.